BIMBINGAN BELAJAR BAGI SISWA YANG KESULITAN DALAM BERHITUNG DI SD NEGERI 15 KARTIASA - Patriana Patriana (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
Counting is an activity of ordering number or counting and recognizing certain quantities, which is a very useful activity in everyday. At elementary school level, some children often have difficulty counting. Difficulty in calculating is like having difficulty answering the question given, such as starting from addition and subtraction questions. The problem formulation based on this phenomenon is about implementing tutoring for students who have difficulty in calculating. The focus of this research is that researchers create tutoring services that suit the needs of students who have difficulty in arithmetic at the high class SD 15 Kartiasa. This research uses a qualitative approach and the type of research is descriptive. Data collection techniques include observation, interviews and documentation. The research results show that first, the steps that teachers must take are identification, diagnosis, prognosis, treatment dan evaluation. Second, the obstacles experienced were a lack of learning media and students inability and third, effords were made tu utilize objects around them and provide questions accordinng to students abilities.